Feed sorting in dairy cattle: Causes, consequences, and management - Miller-Cushon, E.K.; DeVries, T.J. (Journal of dairy science, 2017)
Dairy cattle commonly sort total mixed rations, a behavior that influences individual nutrient intake and reduces the nutritive value of the ration left in the bunk across the day. Typical patterns of feed sorting in lactating dairy cows, against longer forage particles, result in greater intake of highly-fermentable carbohydrates and lesser intake of effective fiber than intended, and are associated with reduced rumen pH and altered milk composition. To understand the reason for this behavior and reduce it on-farm, numerous studies have explored the influences of ration characteristics, feeding strategies, and management factors on the expression of feed sorting. In mature cows and young calves, feed sorting is influenced by forage inclusion rate, particle size, and dry matter content. Feeding strategies that increase the time available to manipulate feed—including decreased feeding frequency and increased feeding level—may result in increased feed sorting. The extent of feed sorting is also influenced by a variety of herd-level factors, but variability between individuals in the extent of feed sorting suggests that this behavior may be subject to additional factors, including previous experience and internal state. The development of feed sorting in young calves has been explored in several recent studies, suggesting that early opportunities to sort feed, as provided by access to mixed diets, may encourage the early onset of this behavior and help it persist beyond weaning. Evidence also supports the role of feedback mechanisms that influence this behavior at the individual level. In calves and adult cows, selective consumption of higher-energy ration components may be linked to energy demands, as influenced by the availability of supplemental feed or changing metabolic status. Further, considerable evidence suggests that cattle will adjust patterns of feed sorting in favor of physically effective fiber to attenuate low rumen pH, providing evidence for the role of postingestive feedback in feed sorting. In general, as long as cattle are provided with mixed diets that satisfy the average nutrient requirements of the group, feed sorting needs to be reduced, either through direct management or by discouraging the early development of the behavior. However, feed sorting may be functional in some scenarios, and continued research is needed to understand the feedback mechanisms that influence feed selection and sorting in young calves, replacement heifers, and mature cows.